KOMUNIKASI STRATEGIK DALAM PENYELESAIAN KONFLIK AGRARIA DI INDONESIA - Yuhdi Fahrimal; Safpuriyadi Safpuriyadi (Jurnal Riset Komunikasi (JURKOM), 2018)
Agrarian conflict between indigenous communities and oil palm plantation companies in Indonesia continues to occur. The expansion of oil palm plantations, claims to land claims, and the overlapping of palm oil plantation permit policy are the cause of the increasing number of agrarian conflicts. This study aims to analyze the communication strategy in the settlement of agrarian conflict in Cot Mee Village, Nagan Raya District. Agrarian conflict between the people of Cot Mee Village and PT. Fajar Baizury & Brothers has been going on for a long time. This conflict is based on land use actions by palm oil plantation corporation claimed by the community as customary land. The settlement efforts are still partial and have not found a common ground. The failure of local government as a mediator is caused by the dilemma position of local government because it is related to local tax revenue from palm oli plantation corporation. In the effort to solve agrarian conflict in Cot Mee Village, Communication Strategic perspective (Silvio Wasibord, 2014) can be used through five stages of strategy formulation; (1) problem definition; (2) goal selection; (3) strategy junctures; (4) tactics; and (5) people's motivations for change.